First clinical application of octacalcium phosphate collagen composite on bone regeneration in maxillary sinus floor augmentation: A prospective, single‐arm, open‐label clinical trial. Issue 1 (13th April 2019) - Miura, Kei‐ichiro; Sumita, Yoshinori; Kajii, Fumihiko; Tanaka, Hidenori; Kamakura, Shinji; Asahina, Izumi
Abstract: The overall objective of this study was to assess the safety and efficacy of OCP/Col as a bone substitute material for bone regeneration during sinus floor augmentation. Maxillary sinus floor augmentation was performed thorough lateral window approach. According to the height of host bone, simultaneous approach (≥5 mm) or staged approach (less than 5 mm) was applied. In this research, clinical findings of dental implant treatment after setting the restorations were set as a primary endpoint in both approaches (infection, inflammation around the implant, movement of the implant, pain, sensory disorder, and bone resorption around the implant body on radiological evaluation.). In staged approach, histological evaluation of bone biopsy specimen was also conducted. As secondary endpoints, hounsfield unit (HU) value, vertical bone height, implant stability quotient (ISQ), and adverse events during the research were evaluated. In all cases, as a primary endpoint, clinical findings after setting the restorations were uneventful with no adverse events. Histological structure demonstrated mature bone derived from OCP/Col. In the ossified area, osteogenesis was observed around OCP granules, and osteoblast‐like cells were arrayed around OCP granules. Osteocyte encapsulation was recognized in the new bone. HU increased over time with both approaches. Vertical bone height significantly increased at 3 months postoperatively, and maintained during follow‐up. ISQ increased with both approaches. In particular, ISQ was significantly increased with the staged approach. This clinical trial demonstrated the safety and efficacy of OCP/Col for bone regeneration in maxillary sinus floor augmentation. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 108B:243–252, 2020.